As influências do direito internacional da água, mais particularmente das soft law, sobre a construção do tratado de cooperação amazônica - Fonseca, Alan Kelson De Lima (2023)
This dissertation analyzes the influences that the Amazonian Cooperation Treaty suffered from the International Water Law. Despite the fact that the Amazonian Cooperation Treaty did not assimilate concepts rooted in International Water Law, such as the definition of an international drainage basin or an international river, it represents a strong expression of international norms, such as environmental preservation and protection, even assuring the sovereignty of the Amazonian States, since that was its main focus. The reasons why the Treaty favored sovereignty lie in the frequent international discourses that preach the internationalization of the Amazonian, under the false premise that the Amazonian States, due to their rulers, would not be able to manage environmental assets, putting the international community at risk, especially in the future maintenance of these assets. The insistence on the expropriation of Amazonian goods, which result from its immense dimensions and fantastic riches of all kinds, have always been a constant in the Amazonian reality, since the first explorations by the colonizers, which is evaluated in the text, in a separate chapter on the Amazonian. The text assesses the environmental issue, from the perspective that it represents a paradigm shift in Law; demonstrates the growing concern of countries with the availability and quality of water, which has generated cross-border international conflicts; reports the terms of construction of the Amazonian Cooperation Treaty and the difficulties in its implementation; and, as a conclusion, evaluates the importance of the rules of International Water Law in the Amazonian Cooperation Treaty, and the strong contribution of the terms of the Treaty in the International Water Law.